Post-activation performance enhancement after inclusion of opponent versus no opponent during isoinertial crossover step exercise: A randomized crossover trial - Arede, J.; Esteves, P.; Blanco, D.; Romero-Rodriguez, D.; Leite, N.; Madruga-Parera, M. (International Journal of Sports Science & Coaching, 2022)
This study sought to determine whether the inclusion of an opponent on an isoinertial crossover step task influenced the post-activation response and power production. Twenty adult male team-sports athletes participated in a randomized crossover trial. We used a novel design in which the performance of an isoinertial flywheel exercise was tested with or without the inclusion of sport-specific constraints (inclusion of an opponent vs. no opponent) in one of the two sequences (sequence one: constraint manipulation followed by no constraint manipulation; and sequence two: no constraint manipulation followed by constraint manipulation). Maximal power was recorded during exercise; then the coefficient of variation of maximal power was estimated. Post-activation responses were measured using unilateral jump height and change-of-direction time. Also, ankle dorsiflexion range of motion was measured. The use of an isoinertial flywheel resulted in improved ankle dorsiflexion and the capacity to repeat change-of-direction. Furthermore, the inclusion of an opponent was associated with a higher variability of the power output in the concentric phase of the movement. Importantly, performing the crossover step task in front of an opponent was also linked to a positive correlation between unilateral countermovement jump and power output. We conclude that the inclusion of typical constraints of the performance environment may have induced movement adaptations to accommodate the unpredictability associated with the actions of the opponent.